The Omicron Variant of SARS-CoV-2 Virus: the Ability to Cause Disease in Persons with Immunity against COVID-19 - T. E. Sizikova; O. V. Chuhralya; V. N. Lebedev; S. V. Borisevich (Вестник войск РХБ защиты, 2023)
During the COVID-19 pandemic the experts noted the emergence and periodic change of the dominant variants of the coronavirus (SARS-CoV-2) that caused the disease. The line B.1.1529, the omicron variant according to the WHO classification, became dominant in the fifth wave of the COVID-19 pandemic. The aim of the work is to analyze the properties of B.1.1529 (omicron) viruses that ensure its ability to cause disease in vaccinated or previously recovered from COVID-19. The fifth wave is characterized by the parallel distribution of the delta and omicron variants, with the domination of the latter. The omicron variant arose as a result of multiple passages of SARS-CoV-2 through the organisms of immunocompromised patients. If the delta variant is the most virulent for humans, the omicron variant is certainly the most infectious - the value of the basic reproductive number (R0) for it is ≈ 10.0, for the delta variant ≈ 6, 0. A person infected with the omicron variant is capable of transmitting the SARS-CoV-2 virus within a day. This is caused by a combination of N501Y and Q498R mutations in the omicron variant, which increase the affinity of the receptor-binding domain of the S1 subunit of the viral S protein for the ACE-2 receptor in the human lung. Mutations H655Y and N679K are located near the furin cleavage site, which in turn promotes accelerated cleavage of the S-protein and increases the level of infectiousness of the pathogen. The omicron variant is significantly superior to the delta variant in terms of ability to overcome the immunity caused by vaccination. The spread of the disease was not stopped by the fact that the number of people who completed the full course of vaccination at the beginning of the fifth wave in Russia reached 64%.Therefore, the achieved level of vaccination cannot be considered sufficient to stop the spread of this variant of the virus. It is shown in the article, that this indicator should be at least 80% to prevent the spread of the disease, and only if vaccination is carried out in a short time. However, it is possible that the mutational potential of the SARS-CoV-2 virus has not yet been exhausted, and the pandemic on the omicron variant will not end.